1999
DOI: 10.1097/00000539-199902000-00039
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Effects of Isoflurane, Sevoflurane, and Propofol on Platelet Aggregation

Abstract: In our study, using vacuum-operated tubes, we demonstrated that sevoflurane and propofol had a significant inhibitory effect on intraoperative and early postoperative platelet aggregation, whereas isoflurane had no effect. Therefore, isoflurane may be preferred as a general anesthetic in patients with a clinically relevant bleeding tendency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 7 publications
2
37
0
Order By: Relevance
“…In an in vitro study performed on blood samples obtained from patients under general anesthesia, Dogan and colleagues showed that sevoflurane and propofol, but not isoflurane, possess significant inhibitory effects on platelet aggregation. 12 Similar results were also obtained by Hirakata et al as they demonstrated that in patients anesthetized with sevoflurane, but not isoflurane, secondary platelet aggregation could not be induced by adenosine diphosphate (ADP) and epinephrine. 13 However, the same group demonstrated in vitro that although isoflurane was less potent than halothane and enflurane, it could inhibit thromboxane A 2 induced platelet aggregation in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 71%
“…In an in vitro study performed on blood samples obtained from patients under general anesthesia, Dogan and colleagues showed that sevoflurane and propofol, but not isoflurane, possess significant inhibitory effects on platelet aggregation. 12 Similar results were also obtained by Hirakata et al as they demonstrated that in patients anesthetized with sevoflurane, but not isoflurane, secondary platelet aggregation could not be induced by adenosine diphosphate (ADP) and epinephrine. 13 However, the same group demonstrated in vitro that although isoflurane was less potent than halothane and enflurane, it could inhibit thromboxane A 2 induced platelet aggregation in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, the same author states that the administration of propofol generates ht decreases between 4-7% of the value obtained after the MPA, results that corroborate those found in this study (3-7%). The isoflurane does not promote hematological changes during trans-and post-operative times (DOGAN et al, 1999). Although there were no hemogasometric evaluations, mechanical ventilation occurred without complications, and as Batista et al (2010) describe, it performed this function without deleterious effects on the cardiovascular system.…”
Section: Introductionmentioning
confidence: 89%
“…49,50 Given the hemodynamic effects of anesthetic drugs, changes in shear stress within the circulation may be expected to modify platelet and PMV behaviour, but there are no published data on how this may affect PMV. Statins have no effect on PMV numbers.…”
Section: Anesthetics and Other Drugsmentioning
confidence: 99%